Employing Camera Traps for Studying Habitat Use by Crocodiles in a Mangrove Forest in Sarawak, Borneo - Mohd Azlan, Jayasilan; J, Zulaiha; Engkamat, Lading; A.A., Nuriza; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2016)
Effective wildlife monitoring for conservation relies on census methods that deliver cost effective and logistically efficient data. Camera trapping has become a common tool in contemporary wildlife science, helping researchers collect images of uncommon or rarely seen and often threatened species as evidence. The development of camera trapping technique has led to significant advancement of the understanding of the diversity of animals and has helped detect secretive species that survive in low densities (e.g., Mohd-Azlan 2003; Mohd-Azlan et al. 2003). However, relatively few studies of crocodilians have employed the technique (Thorbjarnarson et al. 2000; Channa et al. 2010; Charruau and Hénaut 2012; Platt et al. 2014a), and one recent survey reported a lack of success (Platt et al. 2014b), possibly due to lack of technical modification of motion-sensitive infrared cameras (Merchant et al. 2012).